Tinggalan Batu Lumpang di Desa Ruko, Kecamatan Tobelo: Tinjauan Atas Konteks Sejarah dan Sosial Budaya Kerajaan-Kerajaan Lokal di Halmahera Utara - Karyamantha Surbakti (Kapata Arkeologi, 2015)
Batu Lumpang in the archaeological perspecitve is known as remains with the characteristic as a tool for mashing food . This stone has a container shape that made of stone vessels were notched in the middle. The purpose of this study is to initiate the prelimenary study of the batu lumpang in the Ruko village, the District Tobelo , North Halmahera and will be use as a data that assist the interpreationt and explaination on the history of  North Halmahera. The research method adopted in this study is observation and interviews. Qualitative analysis and ethnoarchaeology analysis has been adopted to see the depth of the data to be interpreted. Results of the study shows that the  factors of hegemony of the Ternate empire who conquered Moro and an abundance of food sources in Moro, as well as the strong indication of batu lumpang as the main supporting objects for the  economic activity at that time.Batu lumpang dalam khasanah arkeologi dikenal sebagai tinggalan dengan ciri yang mengarah sebagai alat menumbuk makanan. Batu ini merupakan wadah yang berbentuk bejana terbuat dari batu yang berlekuk di tengahnya. Tujuan dari penelitian ini sebagai studi awal dalam melihat tinggalan batu lumpang yang ada di Desa Ruko Kec. Tobelo Kab. Halmahera Utara sebagai data yang membantu menginterpretasi dan menjelaskan sebuah peristiwa sejarah yang panjang di Halmahera Utara. Metode penelitian menggunakan observasi langsung dan wawancara. Analisis kualitatif dan analisis etnoarkeologi diperlukan untuk melihat kedalaman data yang hendak diinterpretasikan. Hasil dari penelitian adalah faktor hegemoni kekuasaan dari kerajaan Ternate yang menaklukkan kerajaan Moro dan berlimpahnya sumber bahan pangan di Moro menjadikan indikasi kuat batu lumpang sebagai penyokong aktivitas ekonomi pada kala itu.